2008
DOI: 10.1017/s0007114508973827
|View full text |Cite
|
Sign up to set email alerts
|

The distributions and correlates of serum albumin levels in institutionalised individuals with intellectual and/or motor disabilities

Abstract: The serum albumin level is a widely accepted indicator of nutritional status in healthy adults and elderly individuals. However, there are few data regarding the distribution and correlates of serum albumin levels in individuals with intellectual and/or motor disabilities. We conducted a crosssectional study at a public facility for individuals with intellectual and/or motor disabilities in Ibaraki prefecture, Japan. Health check-up data obtained in 2001 from 477 individuals with intellectual disability (286 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…CRP is a sensitive marker of inflammation [ 42 ], and CRP levels were negatively associated with serum albumin in a number of studies [ 43 44 45 46 47 48 49 ]. In the present study, the negative correlation between CRP and serum albumin levels was significant in both the sex- and age-adjusted and multivariable analyses, similar to results from a previous study on individuals with ID [ 23 ]. A negative correlation with inflammation was also observed in individuals with MD.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…CRP is a sensitive marker of inflammation [ 42 ], and CRP levels were negatively associated with serum albumin in a number of studies [ 43 44 45 46 47 48 49 ]. In the present study, the negative correlation between CRP and serum albumin levels was significant in both the sex- and age-adjusted and multivariable analyses, similar to results from a previous study on individuals with ID [ 23 ]. A negative correlation with inflammation was also observed in individuals with MD.…”
Section: Discussionsupporting
confidence: 90%
“…Second, use of medications, particularly antiepileptic drugs, can decrease the capability to synthesize hepatic albumin, and use anticonvulsants and/or major tranquilizers and other medications has been associated with low serum albumin levels in men with ID [ 23 ]; 234 of 249 individuals (94%) in the present study were taking medications. Albumin is synthesized only in liver cells, and its production is quite constant in healthy individuals; therefore, just a small intracellular deposit of protein is needed [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, despite a relatively high proportion (22%) of the participants rated malnourished or at risk of malnutrition, only one of 104 participants was below the threshold of 3·5 g/dl. Poor correlation of serum albumin with nutritional status has also been observed by Ohwada and Nakayama (2008). Their study also observed a relatively low incidence (six of 474 persons, 1·3%) of low serum albumin in institutionalised persons with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 81%
“…Given the primarily caloric nutritional compromise this population experiences, albumin and pre-albumin are generally normal. 15,16 Their normality should not be interpreted as evidence of adequate nutritional status. Low values may be nutritional (chronic lowprotein intake) or non-nutritional (the fluid shifts of an acutely ill patient, protein losses in urine or stool or liver disease).…”
Section: Laboratory Analysismentioning
confidence: 99%